2015
DOI: 10.1007/978-3-662-45704-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors and Risk Cognition in the Discourse on Food-Borne Diseases

Abstract: The aim of this contribution is to discuss the most important issues connected with communicating food-borne diseases. The investigation focuses on the role of symbolic language in informing stakeholders about food-borne crisis situations. To narrow the scope of the research, the study concentrates on metaphors and their role in risk cognition, especially in the face of information overload. This approach allows the author to study the metaphorical dimension of risk cognition as well as its dynamics connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Literature on risk/crisis communication has already shown that the use of metaphorical and visual narratives can be convenient to enable the understanding of complex information, encourage the public's adherence to appropriate behaviours and, combat misinformation (Bielenia-Grajewska, 2015;Lipkus & Hollands, 1999;Shanahan et al, 2019). To analyze the relevance of such uses, the chart entitled "flatten the curve", adopted by science, health and political agents from the beginning of the COVID-19 pandemic, was defined as an object of study.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on risk/crisis communication has already shown that the use of metaphorical and visual narratives can be convenient to enable the understanding of complex information, encourage the public's adherence to appropriate behaviours and, combat misinformation (Bielenia-Grajewska, 2015;Lipkus & Hollands, 1999;Shanahan et al, 2019). To analyze the relevance of such uses, the chart entitled "flatten the curve", adopted by science, health and political agents from the beginning of the COVID-19 pandemic, was defined as an object of study.…”
Section: Introductionmentioning
confidence: 99%